Evaluating Ecosystem Carbon Pools in Coffee-Based Agroforestry under the Framework of the King’s Philosophy for Landscape Restoration - Chattanong Podong; Krissana Khamfong; Supawadee Noinumsai; Sukanya Mhon-ing (Jurnal Sylva Lestari, 2026)
Agroforestry systems are increasingly recognized as multifunctional land-use strategies that contribute to climate change mitigation, ecosystem restoration, and rural livelihoods. This study evaluated ecosystem carbon stocks across three land-use systems at the Phu Phayak Highland Agricultural Development Station, northern Thailand, under the framework of the King’s Philosophy for landscape restoration. The systems comprised: (i) coffee intercropped with Pinus kesiya, (ii) coffee intercropped with Morus alba and associated species, and (iii) monoculture coffee without shade trees. Carbon stocks were quantified in aboveground biomass, belowground biomass, and soil organic carbon using plot-based measurements, allometric equations, and standard soil analyses. Results showed significant differences in carbon sequestration among systems (p < 0.05). The P. kesiya–coffee agroforestry system exhibited the highest aboveground and belowground carbon stocks, reflecting the contribution of fast-growing, deep-rooted shade trees. Although monoculture coffee maintained relatively high soil organic carbon due to intensive soil management practices, its total ecosystem carbon stock remained lower because of limited biomass accumulation. Overall, total ecosystem carbon was greater in tree-based agroforestry systems than in monoculture coffee, highlighting the importance of structural complexity, perennial biomass, and root dynamics in long-term carbon storage. These findings underline that the King’s Philosophy encourages sustainable land use that optimizes ecological restoration potential while enhancing adaptive capacity to climate change in Northern Thailand. By integrating perennial tree cover with agricultural production, coffee-based agroforestry emerges as a climate-resilient land-use model that simultaneously strengthens carbon sequestration, ecosystem stability, and long-term landscape sustainability in upland regions. Keywords: agroforestry systems, biomass accumulation, carbon sequestration, climate change mitigation, soil organic carbon